ANALYSIS OF FINANCIAL DISTRESS USING THE ZMIJEWSKI (X-SCORE) METHOD - Yanti, Novi; Aminda, Renea Shinta; Yudhawati, Diah (Manager : Jurnal Ilmu Manajemen, 2023)
The purpose of this study was to analyze the financial distress of plantation sub-sector companies using the Zmijewski method (X-Score) and to determine the level of accuracy and type of error of the three methods. The population in this study are 19 companies. Then, the samples in this study were obtained using a purposive sampling technique of 44 samples from 11 plantation sub-sector companies listed on the Indonesia Stock Exchange in 2018-2021. The data source used in this study uses secondary data in the form of company financial reports from the official website of the Indonesia Stock Exchange and the websites of each company. The analysis technique used is a quantitative descriptive analysis technique using financial ratios from the Zmijewski method. The results of this study indicate that the Zmijewski method has an accuracy rate of 36%. Two companies experiencing financial distress PT. Jaya Agra Wattie Tbk and PT. Eagle High Plantations Tbk.